Management Strategies and Outcomes of a School-Based Nutritious Meal Program in Indonesia: A Qualitative Case Study at SD Negeri 157 Palembang - Sunari Sunari; Edi Harapan; Hery Setiyo Nugroho (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aimed to analyze the management strategies, the role of human resources, and the effectiveness of the national Nutritious Meal Program at Public Elementary School 157 Palembang. A descriptive qualitative approach was employed. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, students, and Nutrition Service Unit (SPPG) representatives. Implementation was effective, supported by menu planning adhering to national standards, clear task distribution, strong cross-sectoral coordination, and continuous evaluation. The program positively impacted students’ health, concentration, and learning motivation. The research provides an early, in-depth case study of the program’s operational management at a single school, offering granular insight into the practical execution of a new national policy. The school’s management model centered on structured planning, collaboration, and monitoring serves as a replicable framework for ensuring effective and equitable program rollout in other primary schools. The study contributes empirical evidence on successful local-level implementation, highlighting critical managerial and human resource factors that translate national policy into tangible educational and health outcomes.